2013
DOI: 10.1140/epja/i2013-13049-0
|View full text |Cite
|
Sign up to set email alerts
|

The neutron-proton charge-exchange amplitudes measured in the dp → ppn reaction

Abstract: Abstract. The unpolarised differential cross section and the two deuteron tensor analysing powers Axx and Ayy of the dp → {pp}sn charge-exchange reaction have been measured with the ANKE spectrometer at the COSY storage ring. Using deuteron beams with energies 1.2, 1.6, 1.8, and 2.27 GeV, data were obtained for small momentum transfers to a {pp}s system with low excitation energy. The results at the three lower energies are consistent with impulse approximation predictions based upon the current knowledge of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…After each COSY cycle with a duration of approximately 300 s, the beam was alternated between an unpolarised and a tensor polarised one. The tensor polarisation itself was determined by the analysis of the reaction d + p → (pp) + n for which the analysing powers are known [9].…”
Section: Methodsmentioning
confidence: 99%
“…After each COSY cycle with a duration of approximately 300 s, the beam was alternated between an unpolarised and a tensor polarised one. The tensor polarisation itself was determined by the analysis of the reaction d + p → (pp) + n for which the analysing powers are known [9].…”
Section: Methodsmentioning
confidence: 99%
“…There has been an extensive programme using the ANKE spectrometer at the COSY Cooler Synchrotron of the Forschungszentrum Jülich to measure the analysing powers in small-angle deuteron charge exchange on hydrogen, dp → ppn [1]. At low excitation energies of the final diproton system, these measurements have yielded valuable information on the spin-spin amplitudes in large-angle neutron-proton elastic scattering [2].…”
Section: Introductionmentioning
confidence: 99%
“…After acceleration in COSY, the deuteron vector and tensor (P zz ) polarisations could be measured in the EDDA polarimeter [5]. Tight limits were placed on any loss of polarisation during acceleration by measuring in parallel in ANKE the analysing powers for elastic deuteronproton scattering, quasi-free np → dπ 0 , and the dp → 3 He π 0 reaction [3] but subsequent research has shown that the most efficient tensor polarimeter is based upon the charge exchange dp → {pp} s n reaction, where only diproton events {pp} s with low excitation energy are retained [1,3]. The use of this reaction as a tensor polarimeter was first advocated in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…1, is operated in combination with the polarized atomic beam source 11 and the LSP, 3,4 developed at Jülich for double-polarized internal target experiments. 12 The installation allows one to study the recombination of polarized atoms in exchangeable storage cells with different inner surfaces inside a superconducting coil producing a longitudinal magnetic field up to 1 T. Parts of the cold surface of the liquid helium tank are covered by activated charcoal panels for cryogenic pumping to reach pressures ≤10 −8 mbar. The temperature of the cooled storage cell can be varied between 40 and 120 K by controlled heating.…”
Section: Introductionmentioning
confidence: 99%